Effects of low-level laser therapy and intramasseteric triamcinolone on postoperative sequelae following mandibular third molar surgery: A comparative study - Tiwari, Rupali S.; Deshpande, Nupoor; Mundada, Bhushan; Reche, Amit; Madhu, Priyanka Paul; Ranit, Pranoti Pramod; Kotewar, Samrudhi S. (National journal of maxillofacial surgery, 2025)
Introduction: The extraction of impacted third molars is now a standard procedure for oral surgeons. However, it also presents with postoperative sequelae that are difficult for the patients to handle. Hence, to overcome these complications, the present study compares the efficacy of laser therapy and triamcinolone acetonide to find the best treatment modality for patients with such difficulties. Materials and Methods: A prospective, randomized clinical trial was carried out on 60 patients aged 18-30 years requiring impacted third molar extraction. The subjects were grouped into two (n = 30 for each group) to assess pain, trismus, and edema. One group was provided with laser treatment with a continuous wavelength of 650 nm at an energy density of 1.26 J/cm2 and output power of 0.3 W for 60 sec, and the other with triamcinolone acetonide 40 mg/ml postoperatively on day two and 20 mg/ml postoperatively on day seven intraorally into buccal mucosa over the masseter muscle. The assessment was done for days 2 and 7. Statistical Package for Social Sciences version 24.0 was used for data analysis, and the statistical significance established was P < 0.05. Result: After assessment for pain, edema, and trismus, complications were reduced from day two to day seven when the two treatment modalities had statistical differences. It was found that the triamcinolone group had more reduction in complications than the laser group. Conclusion: In its limitations, the study concluded that triamcinolone acetonide acts as a better treatment modality than laser treatment during an assessment.